2015
DOI: 10.1186/s12885-015-1273-2
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of patients with advanced hepatocellular carcinoma treated with sorafenib: a retrospective study of routine clinical practice in multi-institutions

Abstract: BackgroundSorafenib is an orally administered multikinase inhibitor with antiangiogenic and antiproliferative properties. The results of large clinical trials demonstrate that sorafenib prolongs survival and the time to progression of patients with advanced hepatocellular carcinoma (HCC). The aim of the present study was to determine the outcomes of such patients who were routinely treated with sorafenib at multi-institutions in Korea, in contrast to formal clinical trials.MethodsBetween August 2007 and March … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 29 publications
0
15
0
2
Order By: Relevance
“…[27][28][29] Although >80% of subjects experienced SAEs, the majority of these were associated with complications of comorbid liver dysfunction and advanced tumor burden, as has been observed in other studies of patients with CPB HCC, 7,9,11 and treatment-related grade ≥3 events were reported to have occur red in only 28% of patients. [27][28][29] Although >80% of subjects experienced SAEs, the majority of these were associated with complications of comorbid liver dysfunction and advanced tumor burden, as has been observed in other studies of patients with CPB HCC, 7,9,11 and treatment-related grade ≥3 events were reported to have occur red in only 28% of patients.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…[27][28][29] Although >80% of subjects experienced SAEs, the majority of these were associated with complications of comorbid liver dysfunction and advanced tumor burden, as has been observed in other studies of patients with CPB HCC, 7,9,11 and treatment-related grade ≥3 events were reported to have occur red in only 28% of patients. [27][28][29] Although >80% of subjects experienced SAEs, the majority of these were associated with complications of comorbid liver dysfunction and advanced tumor burden, as has been observed in other studies of patients with CPB HCC, 7,9,11 and treatment-related grade ≥3 events were reported to have occur red in only 28% of patients.…”
Section: Discussionmentioning
confidence: 51%
“…To the best of our knowledge, the current retrospective case series is the first analysis of the safety and efficacy of nivolumab in patients with HCC and CPB cirrhosis, which is a growing population with a poor prognosis and limited treatment options. [27][28][29] Although >80% of subjects experienced SAEs, the majority of these were associated with complications of comorbid liver dysfunction and advanced tumor burden, as has been observed in other studies of patients with CPB HCC, 7,9,11 and treatment-related grade ≥3 events were reported to have occur red in only 28% of patients. The overall rates of AEs attributed to nivolumab were similar to the rates reported in CPA HCC cohorts in the CheckMate 040 trial, 23 studies of nivolumab in other solid tumors, 30 and rates reported in the CheckMate 040 trial CPB HCC cohort.…”
Section: Discussionmentioning
confidence: 51%
“…For example, sorafenib is a Raf-1 kinase inhibitor and is the only approved drug therapy for HCC. In patients with advanced or metastatic HCC and compensated cirrhosis, sorafenib offers disease control in ~40% of treated patients, with a time to progression of 5.5 months and a median survival time of 10.7 months, ~3 months longer than that of placebo-treated patients (8). Hence, there is an eagerness to dissect the molecular mechanisms of invasion and metastasis for novel insights and interventions against the recurrence of HCC.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the association between treatment duration and survival, two previous studies have demonstrated that the duration of sorafenib treatment is an independent risk factor for survival. 33,34 These findings suggest that skeletal muscle mass seems to be associated with OS when there is no difference in the duration of sorafenib treatment. However, the duration of sorafenib treatment might be more important for OS than skeletal muscle mass if the duration of treatment differs between patients with LSMM and non-LSMM patients.…”
Section: Discussionmentioning
confidence: 85%
“…The study indicated that presarcopenia is a significant prognostic factor in patients with two or less negative prognostic factors (serum albumin level ≤ 3.5 g/dL, AFP level ≥ 100 ng/mL, the presence of bilateral lesions, or the presence of major portal vein invasion). Regarding the association between treatment duration and survival, two previous studies have demonstrated that the duration of sorafenib treatment is an independent risk factor for survival . These findings suggest that skeletal muscle mass seems to be associated with OS when there is no difference in the duration of sorafenib treatment.…”
Section: Discussionmentioning
confidence: 89%